2023
DOI: 10.3389/fphar.2023.1132388
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the effect of traditional Chinese medicine on the activation of PRRs-mediated NF-κB signaling pathway to inhibit influenza pneumonia

Abstract: Influenza pneumonia has challenged public health and social development. One of the hallmarks of severe influenza pneumonia is overproduction of pro-inflammatory cytokines and chemokines, which result from the continuous activation of intracellular signaling pathways, such as the NF-κB pathway, mediated by the interplay between viruses and host pattern recognition receptors (PRRs). It has been reported that traditional Chinese medicines (TCMs) can not only inhibit viral replication and inflammatory responses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Studies have found that inflammation and oxidative stress also play an important role in the development of pulmonary fibrosis (Cameli et al, 2020;Zhang et al, 2023). Hence, to evaluate the…”
Section: Tan Reduced Inflammation and Oxidative Stress In Mice Lung T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that inflammation and oxidative stress also play an important role in the development of pulmonary fibrosis (Cameli et al, 2020;Zhang et al, 2023). Hence, to evaluate the…”
Section: Tan Reduced Inflammation and Oxidative Stress In Mice Lung T...mentioning
confidence: 99%
“…Subsequent studies demonstrated that activation of the PI3K/Akt signaling pathway promoted polarization of macrophages in COPD from M1 to M2 phenotypes. The ratio of M1 to M2 macrophages following monocyte polarization has been linked to various inflammatory diseases (Zhang et al, 2023), and an elevated ratio of M2 macrophages has been implicated in lung inflammation (Lu et al, 2017). Neutrophil infiltration in the submucous membrane of the airway is the main driver of airway inflammation in COPD and is regulated by helper T cells 17 (Th17) and macrophages.…”
Section: The Pi3k/akt Pathway and Inflammation In Copdmentioning
confidence: 99%
“…LSW is a classic proprietary Chinese medicine with antiinflammatory and analgesic effects (105). Its main components are cow gallstone, musk secretion, toad secretion, pearl shell, realgar, and borneol (106). In PR8-infected cells, LSW significantly down-regulated the expression levels of IL-1b, TNFa, IL-6, and IFN-g.…”
Section: Liu Shen Wanmentioning
confidence: 99%